Optimasi Penjadwalan Damping Mahasiswa Difabel Menggunakan Algoritma Genetika (Studi Kasus PSLD Universitas Brawijaya) - Mukh. Mart Hans Luber; Imam Cholissodin; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Mentoring scheduling for Disabled student is the preparation schedule implementation to a companion who served in the division of working time. On the good scheduling process then will maximize service to disabled students. This scheduling problem is difficult because the number of accompanying relative limited compared to the number of disabled students. The schedule created by the workload evenly to each escort. In this study applied the concepts of problem solving scheduling by using genetic algorithms. Application of genetic algorithm to find the optimal solution. In the settlement of this problem use an integer representation with the length of chromosome 45 genes that each section of the gene showed code mentoring. The method used is the crossover one-cut method of point mutation process, using the method of reciprocal exchange and mutation on the selection process using the method of elitism selection. From the results of testing that has been done optimal parameters obtained using a 100 generation with fitness value 0.966. The final results obtained in the form of a mentoring schedule for 5 days.